VARIABILITAS SIFAT BERBAGAI SIFAT AGRONOMI POPULASI KEDELAI YANG DITANAM PADA DUA JARAK TANAM - Dian Rakhmad; Aslim Rasyad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Soybeans(Glycine max (L.) Merill) is an important food crop that served as an alternative source of protein in Indonesia, due to its very high grain protein content ranging from 40% to 50%. This research is intended to determine genotypic variance components, and heritability of important characters in a soybean population at two planting space. The field experiment was conducted using a randomized block design with 3 replications. Six varieties including Argomulyo, Anjasmoro, Kaba, Burangrang, Gema, Grobogan and three line including KM1, KM-12 and KM25 were grown with two spacing plants, ie, 40cm x 20 cm and 40cm x 15 cm in a plot measuring 3 m in lenght and 2 m in wide. Characters Observed were plant height, flowering date, harvesting date, seed number per plant, grain weight per plant, 100-grain weight, and grain yield  m-2. Generally,the result indicate that all characters vary greatly among genotypes but not significantly different between planting space. Specificaly, genotypes showed high variability in flowering date, harvesting date, grain yield m-2  and 100-grain weight, but not for other traits. The value of genotypic varian components was different from 0 only for flowering date, harvesting date, grain yield m-2 and 100-grain weight. Heritability estimated were diffrent from 0 for flowering date, harvesting date, grain yield m-2 and 100-grain weight, but not for other characters. Keywords : soybean, variability, varians component , heritability